Barriers and drivers to exclusive breastfeeding in Kyrgyzstan: a qualitative study with mothers and health workers - Cath Jackson; Marina Duishenkulova; Nurila Altymysheva; Jyldyz Artykbaeva; Raisa Asylbasheva; Eleonora Jumalieva; Anastasia Koylyu; Sian Lickess; Tursun Mamyrbaeva; Veerle Snijders; Julianne Williams; Tiina Likki (International Breastfeeding Journal)
Abstract Background The WHO/UNICEF global nutrition target for exclusive breastfeeding for six months is at least 70% of infants by 2030. However, global prevalence rates are 48% with variations between countries and within regions. Kyrgyzstan has consistently high early breastfeeding initiation rates, yet exclusive breastfeeding for six months is 46%. This qualitative study addressed two research questions: (1) What are the barriers and drivers for mothers to exclusive breastfeeding in the first six months? (2) What are the barriers and drivers for health workers in primary care facilities to supporting exclusive breastfeeding in the first six months? Methods The study took place from April to June 2023 in five sites (mix of urban and rural). Ten focus group discussions with 40 primary care health workers and 20 in-depth interviews with mothers of a child currently aged 6–12 months who initiated breastfeeding with this child were conducted. Mothers were purposively selected to represent four groups of infant feeding practices in the first six months: (1) exclusive breastfeeding, (2) breastfeeding alongside other fluids/solids, (3) breastfeeding alongside infant formula, (4) breastfeeding followed by switching to formula only. The Capability-Opportunity-Motivation-Behaviour (COM-B) model was the underpinning theoretical framework. Data were analysed using the Framework approach. Results The study uncovered important misperceptions amongst mothers who were not exclusively breastfeeding (groups 2–4). These existed alongside a perceived inability to resolve physical challenges of breastfeeding and social pressure to supplement breastmilk with fluids/solids or formula. Half of all mothers felt uncomfortable breastfeeding in public. Health workers were recommending and supporting women with exclusive breastfeeding during multiple antenatal and postnatal interactions during the initial six months. They were knowledgeable and motivated to do this. Moreover, they felt well supported with training, resources, and legislation with just a few mentioning workplace time or space challenges. Very few doctors appeared to currently be meeting with formula industry representatives. Conclusions This theory-informed qualitative study focusing on mother and health worker perspectives provided important insights into the individual and contextual barriers and drivers to exclusive breastfeeding for the first six months in Kyrgyzstan. These insights have informed recommendations for tailored interventions for both groups.